High HBV-DNA serum levels are associated with type 2 diabetes in adults with positive HBsAg: An observational study - Zhang, Sijia; Zong, Yan; Hu, Yue; Sheng, Yuhan; Xiao, Guangqin (Frontiers in Endocrinology, 2023)
Background: The prevalence of diabetes is higher in hepatitis B virus (HBV)-infected population. We aimed to examine the relationship between different serum HBV-DNA levels and type 2 diabetes in adults with positive HBV surface antigen (HBsAg). Methods: We conducted cross-sectional analyses of data obtaining from the Clinical Database System of Wuhan Union Hospital. Diabetes was defined by self-report of type 2 diabetes, fasting plasma glucose (FPG) ≥7mmol/L, or glycated hemoglobin (HbA1c) ≥6.5%. Binary logistic regression analyses were performed to investigate the factors associated with diabetes. Results: Among 12,527 HBsAg-positive adults, 2,144 (17.1%) were diabetic. Patients with serum HBV-DNA <100, 100-2000, 2000-20000 and ≥20000 IU/mL accounted for 42.2% (N=5,285), 22.6% (N=2,826), 13.3% (N=1,665) and 22.0% (N=2,751), respectively. The risk of type 2 diabetes, FPG ≥7mmol/L and HbA1c ≥6.5% in individuals with highly elevated serum HBV-DNA level (≥20000 IU/mL) were 1.38 (95% confidence interval [CI]: 1.16 to 1.65), 1.40 (95% CI: 1.16 to 1.68) and 1.78 (95% CI: 1.31 to 2.42) times relative to those with negative or lowly elevated serum HBV-DNA (<100 IU/mL). However, the analyses showed no association of moderately (2000-20000 IU/mL) to slightly (100-2000 IU/mL) raised serum HBV-DNA levels with type 2 diabetes (OR=0.88, P=0.221; OR=1.08, P=0.323), FPG ≥7mmol/L (OR=1.00, P=0.993; OR=1.11, P=0.250) and HbA1c ≥6.5% (OR=1.24, P=0.239; OR=1.17, P=0.300). Conclusion: In HBsAg-positive adults, highly elevated level rather than moderately to slightly raised levels of serum HBV-DNA is independently associated with an increased risk of type 2 diabetes.